NFE2-driven neutrophil polarization promotes pancreatic cancer liver metastasis progression - Wenchao Xu; Jianzhou Liu; Qiaofei Liu; Jia Xu; Li Zhou; Zhiyong Liang; Haoran Huang; Bowen Huang; Gary Guishan Xiao; Junchao Guo (Cell Reports)
Summary: Pancreatic cancer liver metastasis is an important factor leading to dismal prognoses. The details of adaptive immune remodeling in liver metastasis, especially the role of neutrophils, remain elusive. Here, combined single-cell sequencing with spatial transcriptomics results revealed that liver metastases exhibit more aggressive transcriptional characteristics and higher levels of immunosuppression compared with the primary tumor. We identified neutrophils_S100A12 (S100 calcium binding protein A12) cells as the pivotal pro-metastatic cluster, specifically distributed at the invasive front of the metastatic lesions. Mechanistically, our findings indicated that nuclear factor erythroid 2 (NFE2) is a key transcription factor regulating neutrophil phenotypic polarization. Metastatic tumors produce transforming growth factor β to activate the SMAD3 pathway within neutrophils, inducing NFE2-driven polarization. NFE2 promotes the transcription of peptidylarginine deiminase 4 by binding to its promoter, leading to the generation of neutrophil extracellular traps at the invasive front. Collectively, our data demonstrate that NFE2-driven neutrophil polarization is a potential target for anti-metastatic therapy.